The role of calcium in the cyclic AMP response to histamine in rabbit cerebral cortical slices. - Al-Gadi, M. (1987)
The effect of calcium on the H1- and H2-receptor components of the cyclic AMP response to histamine in rabbit cerebral cortical slices has been investigated. Removal of calcium ions from the incubation medium during the preparation, preincubation and final incubation of brain slices significantly reduced the cyclic AMP responses to adenosine, histamine and the H2-selective agonist, impromidine. Removal of calcium ions from the incubation medium during only the final incubation with agonists did not influence the responses to adenosine, histamine, impromidine and the H1-selective agonist, 2-thiazolylethylamine. Final incubation of rabbit cerebral cortical slices in calcium-free buffer containing EGTA (1 mM) however, selectively reduced the cyclic AMP responses to the H1-agonists histamine and 2-thiazolylethylamine without affecting the response to impromidine or adenosine. These latter incubation conditions significantly reduced the maximal extent of the augmentation of impromidine- or adenosine-stimulated cyclic AMP accumulation produced by H1-receptor stimulation, without affecting the EC50 values of the H1-agonists. Calcium-free/EGTA conditions did not, however, alter the dose-response parameters for the response to the H2-agonist, impromidine. These data provide further evidence that the two histamine receptor systems affect cyclic AMP accumulation in rabbit cerebral cortical slices by different mechanisms.